Clarification of the Phylogenetic Framework of the Tribe Baorini (Lepidoptera: Hesperiidae: Hesperiinae) Inferred from Multiple Gene Sequences. - Xiaoling Fan; Hideyuki Chiba; Zhenfu Huang; Wen Fei; Min Wang; Szabolcs Sáfián (PLoS ONE, 2016)
Members of the skipper tribe Baorini generally resemble each other and are characterized by dark brown wings with hyaline white spots. These shared characteristics have caused difficulties with revealing the relationships among genera and species in the group, and some conflicting taxonomic views remain unresolved. The present study aims to infer a more comprehensive phylogeny of the tribe using molecular data, to test the monophyly of the tribe as well as the genera it includes in order to clarify their taxonomic status, and finally to revise the current classification of the group. In order to reconstruct a phylogenetic tree, the mitochondrial COI-COII and 16S genes as well as the nuclear EF-1α and 28S genes were analyzed using parsimony, maximum likelihood, and Bayesian inference. The analysis included 67 specimens of 41 species, and we confirmed the monophyly of Baorini, and revealed that 14 genera are well supported. The genus Borbo is separated into three clades: Borbo, Pseudoborbo, and Larsenia gen. nov. We confirmed that Polytremis is polyphyletic and separated into three genera: Polytremis, Zinaida, and Zenonoida gen. nov., and also confirmed that the genus Prusiana is a member of the tribe. Relationships among some genera were strongly supported. For example, Zenonia and Zenonoida were found to be sister taxa, closely related to Zinaida and Iton, while Pelopidas and Baoris were also found to cluster together.